2008
DOI: 10.4161/cbt.7.12.6941
|View full text |Cite
|
Sign up to set email alerts
|

Two different HPV-11E6 fusion proteins trap p53 in the cytoplasm and induce apoptosis

Abstract: Mucosal high risk human papillomaviruses (HPVs) have been shown to be the major cause of cervical cancer. However, the reason why the low risk HPVs only cause proliferative but non-invasive lesions of infected epithelia remains elusive. Because p53 interacts with high risk HPVs E6 and plays a very important role in carcinogenesis, it is assumed that low risk HPVs E6 might interact with p53 in a different pattern. We used mammalian green fluorescent protein (GFP) tagged and polyhistidine (His) tagged proteins e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
9
1
Order By: Relevance
“…The calculated molecular mass of E6 is approximately 20 kDa and should allow for the passive diffusion of this small protein through the nuclear pore. However, it was shown that E6 proteins from HPV16, -18, and -31 are predominantly nuclear whereas those from HPV6 and -11 are localized mainly in the cytoplasm (35,37,41,57,59,60,63), although one study showed that HPV11 E6 could be found in both the nucleus and the cytoplasm (24). HPV16 E6 was shown to interact in vitro with the karyopherins ␣2, ␤1, and ␤2 (37), suggesting that E6 is actively imported in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated molecular mass of E6 is approximately 20 kDa and should allow for the passive diffusion of this small protein through the nuclear pore. However, it was shown that E6 proteins from HPV16, -18, and -31 are predominantly nuclear whereas those from HPV6 and -11 are localized mainly in the cytoplasm (35,37,41,57,59,60,63), although one study showed that HPV11 E6 could be found in both the nucleus and the cytoplasm (24). HPV16 E6 was shown to interact in vitro with the karyopherins ␣2, ␤1, and ␤2 (37), suggesting that E6 is actively imported in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that this difference is not due to an inability of low-risk E6 to interact with p53 (11,17,34) or E6AP (5). It has also been suggested that the subcellular localiza-tion of E6 is essential for its p53 degradation activity, based on the observation that high-risk HPV16, -18, and -31 E6 proteins can localize to the nucleus after transfection whereas low-risk HPV6 and -11 E6 proteins are predominantly cytoplasmic (35,37,41,57,59,60,63), although HPV11 E6 has also been detected in the nucleus (24). In another study, the expression levels of E6 have been shown to vary between high-and low-risk types (31).…”
mentioning
confidence: 99%
“…In contrast, none of the low-risk HPV E6 proteins have this motif (53). Moreover, a study presented by Sun et al suggests that trapping of p53 in the cytosol by HPV-11E6 results in apoptosis and represents a novel mechanism to explain why low-risk HPV infection does not result in malignant transformation; this explanation remains tentative, and awaits further testing (54). The best characterized high-risk HPV-16 E6 activity is its ability to induce degradation of the tumor-suppressor protein p53 via the ubiquitin/proteasome pathway.…”
Section: Hpv In Cervical Cancermentioning
confidence: 99%
“…In this issue of Cancer Biology and Therapy 14, Sun and colleagues present data that explores the reasons why low risk HPVs cause non-invasive lesions of infected primary epithelia. Since interaction with and degradation of p53 by the high risk HPV-E6 proteins is key to cellular transformation induced in response to infection with high risk HPV, Sun and coworkers hypothesized that the E6 proteins from low risk HPV might interact differently with p53, and exert different regulatory influences on this tumor suppressor protein.…”
mentioning
confidence: 99%